Electrical behavior of BaSnO3 bulk samples formed by slip casting: Effect of synthesis methods used for obtaining the ceramic powders - Ochoa Muñoz, Yasser Halil (2016)
In order to build bulk pieces using the slip casting technique, barium stannate (BaSnO3) ceramic powders were synthesized using two chemical methods (controlled precipitation and Pechini). Differences in the electrical behavior of the pieces, depending on the synthesis method employed, were then determined. For the analysis, a stable suspension of the synthesized ceramic powder (or 57.6% solids slip) was obtained using water as solvent; the slip was poured into a mold to produce parallelepiped shaped green pieces. The electrical behavior in air at 300 C was determined for pieces sintered using a range of temperatures. The results of this electrical characterization showed that the method of synthesis has strong effects on the electrical behavior of the sintered samples